2022
DOI: 10.1021/acsbiomaterials.1c01044
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Probe Bonding and Fluorescence Properties through Annealed Graphene Oxide Nanosheets

Abstract: Graphene oxide (GO) has been widely used in biological sensing studies because of its excellent physical and chemical properties. In particular, the rich functional groups on the surface of GO can effectively enhance the bonding of biomolecules and serve as an efficient sensing substrate. However, when biomolecules are labeled with fluorescence, the GO interface affects the biomolecules by reducing the fluorescence properties and limiting their applications in biosensing. Here, we establish an annealed GO (aGO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
(56 reference statements)
0
5
0
Order By: Relevance
“…The annealing of GO is a simple heat treatment procedure that can achieve GO reduction. Chen et al enhanced the fluorescence properties of GO by annealing NGO under certain conditions (at 80 °C for 9 days) [ 20 ]. The results revealed that the annealing process can keep the content and distribution of oxygen functional groups in the GO structure efficiently, so that the 2D plane of GO contains both sp 2 and sp 3 clusters simultaneously, but the annealing time is longer.…”
Section: Luminescence Mechanismmentioning
confidence: 99%
See 2 more Smart Citations
“…The annealing of GO is a simple heat treatment procedure that can achieve GO reduction. Chen et al enhanced the fluorescence properties of GO by annealing NGO under certain conditions (at 80 °C for 9 days) [ 20 ]. The results revealed that the annealing process can keep the content and distribution of oxygen functional groups in the GO structure efficiently, so that the 2D plane of GO contains both sp 2 and sp 3 clusters simultaneously, but the annealing time is longer.…”
Section: Luminescence Mechanismmentioning
confidence: 99%
“…GO has been applied in many fields [ 84 ], such as fluorescence imaging [ 16 ], luminescence carriers [ 85 ], sensing matrices [ 20 ], biosensing [ 86 , 87 ], disease detection [ 88 ], drug carriers [ 89 ], ion detection [ 90 ], fluorescent probing [ 91 ], etc., due to its excellent PL properties. In this section, the PL of GO, GQDs, and GOQDs in electronic devices and biomedical fields will be emphatically introduced.…”
Section: Applications Of Go Gqds and Goqds Luminescencementioning
confidence: 99%
See 1 more Smart Citation
“…As proved by XPS analyses, in the reported experimental conditions, the extent of the π-conjugated domains increases whilst the oxygen content and the morphology, investigated by means of SEM and AFM microscopies, remain almost the same, compared to the starting GO material. 12 Finally, Singh et al have demonstrated very recently that heat treatment of GO at 200 °C is the most effective option for developing a porous structure. 16 …”
Section: Introductionmentioning
confidence: 99%
“…and X = C and/or N, and T x represents the terminal groups OH, F, or O) are another emerging area of interest for biochemical sensing applications, owing to their unique planar structure and ability to be functionalized using bioinspired techniques, such as mussel-inspired polydopamine surface coatings on graphene quantum dots for optical imaging. In this issue, Chen and co-workers describe the fabrication of an annealed graphene oxide (aGO)-based biosensor, which uses the effect of redistribution of the oxygen functional groups to achieve enhanced bonding of a DNA probe on the GO nanosheet. Using this annealing technique, the authors have reported an enhancement factor of ∼19.6× for the aGO probes, compared to untreated GO, with the added benefit of higher stability of the aGO probes against fluorescence quenching under laser confocal microscopy.…”
mentioning
confidence: 99%